Rehabilitasi Tebing Sungai Guo Akibat Banjir Bandang di Area Bypass Kota Padang - Nurhamidah Nurhamidah; Ahmad Junaidi; Rudy Ferial; Masril Syukur; Anisa Salsabila M (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
After an earthquake hit the West Sumatra Province in 2009, Padang, as the provincial capital, moved the centre of its government activities to Bypass. Following the government's relocation, the community also moved to the Bypass area. Gradually this caused the area, which was initially a rain catchment area, to turn into a residential and office area. The loss of rain catchment areas increases the amount of runoff drastically. On August 18, 2021, the flood incident was also the cause of flash floods that hit many areas in Padang City, one of which was the Guo River area. The impact of this flood destroyed the cliffs of the Guo River. The cliffs were damaged due to sediment carried from upstream of the Guo River in the form of large rocks and the swift flow of water hitting the cliff walls of the Guo River. Not only destroying the cliff walls but also the access roads around the upper reaches of the Guo River. Therefore, Andalas University and the Guo River community members carried out rehabilitation activities for the Guo River. It was started by survey activity of the level of damage from the collapsed cliff. This was followed by sustainable planning related to the rehabilitation of the cliffs of the Guo River area and planned activities to be carried out to increase and develop it's potential as a natural tourist attraction.